Preceding crop rotation systems shape the selection process of wheat root-associated bacterial communities - Shuting Yu; Tianshu Wang; Li Wang; Shuihong Yao; Bin Zhang (Journal of Integrative Agriculture, 2025)
Wheat–maize (WM) and wheat–soybean (WS) double-cropping rotation systems are predominant in the North China Plain, with implications for national agricultural output and sustainability. As rotation systems exert legacy effects on soil health and crop productivity, the role of crop rotation in shaping the root-associated microbiome of the succeeding crops has emerged as a pivotal aspect of crop management research. Here, the effects of the preceding two cycles of WM and WS rotations on the recruitment and filtering of wheat root-associated bacterial communities across wheat developmental stages were investigated. Our results revealed that bacterial community diversity and composition were primarily influenced by compartment and developmental stage, while the preceding rotation systems had a slight but significant effect on wheat root-associated bacterial communities. The co-occurrence networks under WM were more complex in the wheat rhizosphere and rhizoplane, with the operational taxonomic units (OTUs) related to cellulolysis showing greater connectivity. The co-occurrence networks under WS were simple but stable in the rhizosphere and complex in the rhizoplane and endosphere, with the OTUs related to ureolysis and nitrogen fixation showing greater connectivity. While both stochastic and deterministic processes contributed to the assembly of wheat root-associated bacterial communities, the contributions of deterministic processes under WS were 19.4–38.5% higher than those under the WM rotation across the root-associated compartments, indicating the substantial impact of a soybean legacy effect on wheat root selection of microbes. Plant growth-promoting rhizobacteria with the potential to fix nitrogen, produce indole-3-acetic acid, and inhibit diseases such as Betaproteobacteriales, Azospirillales and Dyella sp., were identified within the OTUs that were consistently enriched across all the wheat root-associated compartments and developmental stages, which were also important predictors of wheat yield. This study elucidates the role of crop rotation in modulating the dynamics of crop root-associated bacterial communities, and underscores the potential of targeted microbiome manipulation for optimizing wheat production and enhancing soil health.